The Effect of Sukuk Structure and Sukuk Guarantee Status on Sukuk Rating in Indonesia Stock Exchange - Kiran Salsabilah; Abdul Hamid Habbe; Nirwana Nirwana (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
This research aims to analyze the effect of sukuk structure and sukuk guarantee status on sukuk rating. The research was conducted based on companies in the financial sector and non-financial sector listed on the Indonesia Stock Exchange and included in the rating conducted by PT Pefindo for the period 2015-2019. A total of 65 samples were selected using purposive sampling method. The data source in this study is secondary data in the form of the company's annual financial statements. The data analysis methods used are ordinal logistic regression analysis The results showed that the sukuk structure has an opportunity to lower the sukuk rating, while the sukuk guarantee status has the opportunity to increase the sukuk rating. Then for simultaneous test results, sukuk structure and sukuk guarantee status have an effect on sukuk rating.